Las coaliciones de izquierdas en Francia y España (1899-1939) - Antonio Robles Egea (Cahiers de Civilisation Espagnole Contemporaine)
Lefts Coalitions created by the Republicans, Radicals, Socialists and Communists in France and Spain, during the first four decades of the twentieth century, constituted an example of political action in defense of modernization and democratization against authoritarian attacks from conservative and totalitarian parties. These coalitions reflected the symbiosis of popular and working classes through the signed agreements between its political organizations. The major objective of the mutual convergence was the formation of a model of democratic and social State